2015
DOI: 10.1192/bjp.bp.114.152082
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of time-limited individual placement and support: IPS-LITE trial

Abstract: IPS-LITE is equally effective to IPS and only minimal extra employment is gained by persisting beyond 9 months. If released capacity is utilised with similar outcomes, IPS-LITE results in an increase by 17% in numbers gaining employment within 18 months compared to IPS and will increase with prolonged follow-up. IPS-LITE may be more cost-effective and should be actively considered as an alternative within public services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 17 publications
4
20
3
Order By: Relevance
“…In this regards, we found a mean of total days employed (about 232 days) that is higher than those reported in the EQUOLISE study (214 days in an 18‐month follow‐up period) (Burns et al, ) and in other European IPS researches [eg, 74 days in a 12‐month follow‐up period (Burns et al, ), 123 days in a 30‐month follow‐up period (Michon et al, )]. Similarly, in the current study, both mean of hours per week worked (~20 hours/week) and job tenure (ie, the mean of weeks worked on the longest‐held competitive job) (about 30 weeks) are definitely greater than those observed in a UK 12‐month follow‐up trial (respectively, 15 hours/week and 18 weeks) (Burns et al, ). Finally, in the present research, consistently with what reported in other US IPS trials (Bond et al, ; Bond, Drake, & Becker, ), almost two‐thirds of IPS workers worked 20 hours or more per week at some time during the 36 months of follow‐up.…”
Section: Discussioncontrasting
confidence: 52%
“…In this regards, we found a mean of total days employed (about 232 days) that is higher than those reported in the EQUOLISE study (214 days in an 18‐month follow‐up period) (Burns et al, ) and in other European IPS researches [eg, 74 days in a 12‐month follow‐up period (Burns et al, ), 123 days in a 30‐month follow‐up period (Michon et al, )]. Similarly, in the current study, both mean of hours per week worked (~20 hours/week) and job tenure (ie, the mean of weeks worked on the longest‐held competitive job) (about 30 weeks) are definitely greater than those observed in a UK 12‐month follow‐up trial (respectively, 15 hours/week and 18 weeks) (Burns et al, ). Finally, in the present research, consistently with what reported in other US IPS trials (Bond et al, ; Bond, Drake, & Becker, ), almost two‐thirds of IPS workers worked 20 hours or more per week at some time during the 36 months of follow‐up.…”
Section: Discussioncontrasting
confidence: 52%
“…Recent trial evidence suggests that time-limiting IPS services to nine months support delivers similar employment outcomes as a time-unlimited service but in a significantly more cost-efficient manner. 17 This proposed fifteen month maximum balances these positions, is in line with broader international thinking on employment programme duration, and offers slightly greater flexibility to the service to achieve outcomes compared to that very rapid nine month duration. The target cohort in mind is individuals with mild to moderate mental health and/or physical health conditions in primary health care or community settings.…”
Section: Estimating Modified Ips Service Costsmentioning
confidence: 72%
“…Furthermore, Yang and colleagues [40] suggested that not the PD diagnosis itself but the severity of the symptoms is positively related to the extent of occupational impairment. In line with most previous IPS trial samples [41][42][43][44], predominantly men were included in the present study. We did not identify previous studies examining the question as to why males are overrepresented in most IPS samples.…”
Section: Interpretation Of the Study Findings And Comparison With Thementioning
confidence: 92%